Reducing the effect of engine failure on the aerodynamic performance of the light transport aircraft model - Yu. S. Mikhailov (Научный вестник МГТУ ГА, 2024)
Recently, aircraft engine manufacturers have shown increased interest in developing hybrid powerplants, which are a combination of gas turbine engines (GTE) with electric motor-generators. The use of the hybrid powerplant makes it possible to increase the fuel efficiency of an airplane, as well as to create new configurations with improved aerodynamic and thrust characteristics. The fuel efficiency improvement is achieved as a result of optimizing the powerplant operation mode to meet the cruising flight requirements, compensating insufficient power during the takeoff and go-around procedures by activating battery-powered electric motors. The creation of new configurations with improved performance can be ensured due to the synergetic effect of the propeller-airframe interaction. Successful flight tests of the hybrid powerplant prototypes in light aircraft configurations allow us to rely on their possible application in the future regarding the projects of new propeller-driven aircraft. The potential benefits of using new powerplants on local airlines can lead to both fuel savings and carbon emission reduction. Short-term maintaining a safe flight mode is also practical in case of one engine failure when using multiple power sources. The power, generated by an electric generator connected to the running engine, can be used both for the electric motor drive of the tip propellers and for rotating the thrust producer of the failed engine. The paper presents the study results of the critical engine failure effect on the aerodynamic performance of the light transport aircraft model obtained as under available electrical transmission as under non-available one between a running and a failed engine. Experimental studies were carried out in a low-speed wind tunnel T-102 TsAGI. The simulation of the electric transmission operation was carried out by setting the operation mode of two power-plant simulators corresponding to the half value of the load factor of one engine propeller Bo in the take-off mode.